Cortical suspensory endobutton versus aperture interference screw fixation for arthroscopic anterior cruciate ligament reconstruction using hamstring graft: a prospective study - B., Tejaswi K.; C., Satish Kumar; Patwegar, Abdul Qadeer; M., Lohith (International Journal of Research in Medical Sciences, 2023)
Background: Anterior cruciate ligament injury is a common injury which occurs in sports with an annual incidence of 68.6% per 100,000 population. Anatomic arthroscopic reconstruction remains the main stay treatment of ACL injury. Fixation of graft is classified as direct and indirect. To compare the stability of knee joint, complications in arthroscopic anterior cruciate ligament reconstruction by aperture interference screw fixation versus suspensory device fixation in femur. Methods: The randomized control study was conducted in department of orthopedics, The Oxford Medical College Hospital and RC from 2020-2021. 30 knees were operated, Ethical clearance taken and patient is followed up for six months. Results: The preoperative Tegner Lysholm knee score was poor in both groups. Post-op in interference screw group, 12 patients 80% had excellent functional outcome, 3 patients 20% had good outcome. In the Endbutton group, 11 patients (73%) had excellent outcome while 4 patients (27%) had good outcome. Conclusions: Suspensory device fixation gives equivalent results when compared to aperture screw fixation. complications of screw fixation were graft rupture cyst formation; complications of suspensory devices were loosening of graft and bungee cord effect. Hence, Both the techniques showed no statistical difference in post operative outcome.